On the convergence of evolutionary and behavioral theories of organizations: A tentative roadmap - Giovanni Dosi; Luigi Marengo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
The behavioral theory of the firm has been acknowledged as one of the most fundamental pillars on which evolutionary theorizing in economics has been built. Nelson and Winter's 1982 book is pervaded by the philosophy and concepts previously developed by Cyert, March and Simon. On the other hand, some behavioral notions, such as bounded rationality, though isolated from the context, are also at the heart of some economic theories of institutions such as transaction costs economics. In this paper, after briefly reviewing the basic concepts of evolutionary economics, we discuss its implications for the theory of organizations (and business firms in particular), and we suggest that evolutionary theory should coherently embrace an embeddedness view of organizations, whereby the latter are not simply efficient solutions to informational problems arising from contract incompleteness and uncertainty, but also shape the visions of the world, interaction networks, behavioral patterns and, ultimately, the very identity of the agents. After outlining the basic features of this perspective we analyze its consequences and empirical relevance.
Keywords: 330; Evolutionsökonomik; Verhalten in Organisationen; Lernende Organisation; Theorie der Unternehmung; Theorie